2013
DOI: 10.1016/j.ab.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a SIRT6 open tubular column: Predicting deacetylation activity using frontal chromatography

Abstract: SIRT6 is a histone deacetylase that has been proposed as a potential therapeutic target for metabolic disorders and the prevention of age-associated diseases. Thus the identification of compounds that modulate SIRT6 activity could be of great therapeutic importance. We have previously reported on the identification of quercetin and vitexin as SIRT6 inhibitors, using SIRT6-coated magnetic beads. In this study, we have immobilized SIRT6 onto the surface of an open tubular capillary and characterized the querceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 18 publications
(23 reference statements)
3
55
1
1
Order By: Relevance
“…We have previously demonstrated that a series of flavanoids had significant inhibitory effects on the deacetylation activity of SIRT6 [13] , as a result, quercetin and luteolin were used as positive controls. Both quercetin and luteolin inhibited SIRT6 deacetylase activity in a concentration-dependent manner (Table 1), with an IC 50 value of 24 μM and 4.1 μM, respectively, consistent with previous reported values [13a, 17] . Further, they both inhibited SIRT6 deacetylation activity to a similar extent (38 and 30%, respectively).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We have previously demonstrated that a series of flavanoids had significant inhibitory effects on the deacetylation activity of SIRT6 [13] , as a result, quercetin and luteolin were used as positive controls. Both quercetin and luteolin inhibited SIRT6 deacetylase activity in a concentration-dependent manner (Table 1), with an IC 50 value of 24 μM and 4.1 μM, respectively, consistent with previous reported values [13a, 17] . Further, they both inhibited SIRT6 deacetylation activity to a similar extent (38 and 30%, respectively).…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, while quercetin and luteolin both elicited a dose-dependent inhibition of SIRT6 deacetylation activity as previously reported [17] , they also displayed significant increase (6-10 fold) of SIRT6 deacetylation activity at higher doses. The identification of NAEs and the flavonoids as activators of SIRT6 expands the multiple roles of SIRT6.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The extract was prepared by HerbPharm as previously described [12]. T. foenum-graecum seed was extracted by maceration for 3 weeks at 1:2.5 ratio at 72% ethanol, ratio expressed as mass raw plant material ( T. foenum-graecum seed) in weight (g) per volume (mL) of extraction solvent.…”
Section: 2 Methodsmentioning
confidence: 99%
“…Cytosolic proteins are usually covalently bonded using their N-or C-terminus groups forming the covalent bond with chemical moieties on the surface of the assay scaffold, e.g. the inside of the column or magnetic beads [9,10]. Many natural compounds target cell membrane proteins but the solutions developed for cytosolic proteins cannot be used to immobilize transmembrane proteins [7].…”
Section: Introductionmentioning
confidence: 99%